Learning a Lesson: Spiritual Attributions of Sexual Trauma and Revictimization - Eytan, Sharon (International journal of offender therapy and comparative criminology, 2023)
This study aims to explore how individuals with affiliation to spirituality and victimization attribute sexual trauma and revictimization to spiritual principles and its perceived impact on victim assistance. A phenomenological research was conducted with 36 participants divided into three groups: female survivors who turned to spirituality as part of their recovery process (n = 17), spiritually oriented therapists who treat survivors (n = 10), and spiritual leaders and teachers who are often consulted by survivors and their close ones (n = 9). Findings show three prominent themes: (a) ephemeral and eternal components of existence; (b) learning a lesson; and (c) Tikkun Olam (Hebrew: world’s repairment). The findings contribute theoretical and practical applications: they offer deep insights into the spiritual reason for revictimization and its cessation, and suggest innovative external explanations anchored in ancient knowledge that can alleviate survivors’ suffering from self-blame. The study lays the foundation for an upcoming theory entitled Spiritual Victimology.